Smart glasses for monitoring vital signs in anaesthesia care settings : a qualitative simulation study - Enlöf, Per; Sjöberg, Carina; Ringdal, Mona; Lindgren, Sophie; Wolf, Axel; Jildenstål, Pether (BMC Anesthesiology, 2025)
BACKGROUND: Monitoring of vital signs is essential in anaesthesia care and plays a key role in preventing adverse events. Technological innovation is recognised as an important factor in enhancing patient safety. Smart glasses represent a novel tool that may support anaesthesia professionals in monitoring vital signs; however, their practical use and user experiences in anaesthesia care remain insufficiently explored. Understanding anaesthesia healthcare professionals' experiences with this technology is crucial to ensure its safe and effective implementation. In this study, smart glasses from Microsoft HoloLens 2 were used to visualize vital signs in the user's field of vision. The aim was to explore anaesthesia health care professionals' experience of using Microsoft HoloLens 2 smart glasses for monitoring vital signs in various simulated anaesthesia care scenarios. METHODS: A qualitative study design was used to explore the experiences of nurse anaesthetists and anaesthesiologists. Data were gathered through focus group interviews and subsequently analysed using qualitative content analysis. RESULTS: One overarching theme - a positive yet cautious attitude towards smart glasses - was identified, comprising three categories: Impact on intraoperative monitoring, Usability of the smart glass technology, and Communication challenges. These categories illustrated both advantages and limitations of using smart glasses in simulated anaesthesia care scenarios. CONCLUSIONS: The experience of using Microsoft HoloLens 2 for monitoring vital signs in simulated anaesthesia care scenarios revealed a generally positive but careful attitude towards the technology. Participants appreciated its potential to enhance situational awareness through continuous access to vital signs, while also highlighting concerns related to ergonomics, restricted field of view, and possible distraction. The findings offer insights for developers aiming to optimise smart glasses for clinical use. Further refinement and evaluation in clinical settings are needed before broader implementation in anaesthesia practice.
© 2025. The Author(s).
Keywords: Humans; Vital Signs/physiology; Qualitative Research; Smart Glasses; Anesthesiologists; Nurse Anesthetists; Monitoring, Intraoperative/methods; Attitude of Health Personnel; Focus Groups; Anesthesia/methods; Female; Male; Monitoring, Physiologic/methods